2015
DOI: 10.2460/javma.247.8.938
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of clinical veterinarians at a US veterinary teaching hospital regarding antimicrobial use and antimicrobial-resistant infections

Abstract: Findings indicated that veterinarians at this teaching hospital were concerned about antimicrobial resistance, thought antimicrobials were overprescribed, and supported restricting use of certain antimicrobial classes in companion animals. Findings may be useful in educating future veterinarians and altering prescribing habits and antimicrobial distribution systems in veterinary hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 19 publications
4
26
1
Order By: Relevance
“…Cost, owner compliance, animal-related factors, the non-healing nature of a given infection, and the desire to adhere to best practices were the primary themes influencing veterinary C/S test ordering behaviours in this study. Previous studies on antimicrobial prescribing practices suggest that human factor-related barriers to judicious use such as ease of administration and perceived owner compliance play a key role in resistance emergence (Mateus and others 2014, Bender 2015, Bender and others 2015a,b, Jacob and others 2015). Two Canadian studies used focus group interview with veterinarians and clients to assess factors related to veterinarian-client communication as well as monetary concerns in practice (Coe and others 2007, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cost, owner compliance, animal-related factors, the non-healing nature of a given infection, and the desire to adhere to best practices were the primary themes influencing veterinary C/S test ordering behaviours in this study. Previous studies on antimicrobial prescribing practices suggest that human factor-related barriers to judicious use such as ease of administration and perceived owner compliance play a key role in resistance emergence (Mateus and others 2014, Bender 2015, Bender and others 2015a,b, Jacob and others 2015). Two Canadian studies used focus group interview with veterinarians and clients to assess factors related to veterinarian-client communication as well as monetary concerns in practice (Coe and others 2007, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…While a number of studies have assessed the factors influencing antimicrobial prescribing practices of physicians and other human healthcare providers (Morley and others 2005, Isturiz 2010, Escher and others 2011, Mateus and others 2011, Hughes and others 2012, Coyne and others 2014, Mateus and others 2014, Riviere and Fink-Gremmels 2014, Bender and others 2015a, b , Butterweck 2015, Jacob and others 2015), there have been few studies describing antimicrobial prescribing by veterinarians (De Briyne and others 2013, 2014, Summers and others 2014, Schwechler and others 2016). One study of prescribing physicians found that concerns about and factors impacting antimicrobial prescribing practices differed dramatically by job title or specialty, and concluded that interventions would need to be tailored to each specialty group in order to improve antimicrobial stewardship (Schweizer and others 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Missing data was treated as such. Antimicrobial drugs were ranked from most to least used and were grouped by name into similar classes as described previously (Green et al 2010;Jacob et al 2015). The commonly prescribed antimicrobial drugs were grouped into medically important antimicrobial classes as grouped by the United States Food and Drug Administration (FDA 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Veterinarians in another U.S. veterinary teaching hospital believed antimicrobials were over-prescribed in veterinary practice. The veterinarians in that hospital (Jacob et al 2015) were concerned about AMR and supported the idea of restricting the use of certain antimicrobial classes in companion animals. Prior to this study, the factors that influenced University of Tennessee Veterinary Medical Center (UTVMC) clinicians to start, delay, or discontinue the use of antimicrobials and/or to determine the class of antimicrobials used were unknown.…”
Section: Introductionmentioning
confidence: 99%